Cosmic spherules from Widerøefjellet, Sør Rondane Mountains (East Antarctica) - Goderis, Steven; Soens, Bastien; Huber, Matthew S.; McKibbin, Seann; van Ginneken, Matthias; Van Maldeghem, Flore; Debaille, Vinciane; Greenwood, Richard C.; Franchi, Ian A.; Cnudde, Veerle; Van Malderen, Stijn; Vanhaecke, Frank; et al. (Geochimica et Cosmochimica Acta, 2020)
A newly discovered sedimentary accumulation of micrometeorites in the Sør Rondane Mountains of East Antarctica, close to the Widerøefjellet summit at ∼2750 m above sea level, is characterized in this work. The focus here lies on 2099 melted cosmic spherules larger than 200 μm, extracted from 3.2 kg of sampled sediment. Although the Widerøefjellet deposit shares similarities to the micrometeorite traps encountered in the Transantarctic Mountains, both subtle and more distinct differences in the physicochemical properties of the retrieved extraterrestrial particles and sedimentary host deposits are discernable (e.g., types of bedrock, degree of wind exposure, abundance of metal-rich particles). Unlike the Frontier Mountain and Miller Butte sedimentary traps, the size fraction below 240 μm indicates some degree of sorting at Widerøefjellet, potentially through the redistribution by wind, preferential alteration of smaller particles, or processing biases. However, the cosmic spherules larger than 300 μm appear largely unbiased following their size distribution, frequency by textural type, and bulk chemical compositions. Based on the available bedrock exposure ages for the Sør Rondane Mountains, extraterrestrial dust is estimated to have accumulated over a time span of ∼1–3 Ma at Widerøefjellet. Consequently, the Widerøefjellet collection reflects a substantial reservoir to sample the micrometeorite influx over this time interval. Petrographic observations and 3D microscopic CT imaging are combined with chemical and triple-oxygen isotopic analyses of silicate-rich cosmic spherules larger than 325 μm. The major element composition of 49 cosmic spherules confirms their principally chondritic parentage. For 18 glassy, 15 barred olivine, and 11 cryptocrystalline cosmic spherules, trace element concentrations are also reported on. Based on comparison with evaporation experiments reported in literature and accounting for siderophile and chalcophile element losses during high-density phase segregation and ejection, the ...